(untitled) (American Journal of Islam and Society, 2019)
Since 9/11, second-generation Muslims have experienced an increase in religious discrimination that has presented several challenges to their American integration. Scholars have noted that Muslims are often marginalized and “othered” because of their religious beliefs, attire choices and non-Western ethnic origins. In New York, Arabs, South Asians and Africans are the predominant ethnic groups practicing Islam. Although Muslim communities are ethnically and racially diverse, they are categorized in ways that have transformed their religious identity into a racialized group. This new form of racial amalgamation is not constructed on underlying skin color similarities but on their religious adherence to Islam. The War on Terror has complicated the image of Muslims by circulating Islamophobia, or the fear of Muslims and Islam, onto American society. Political rhetoric targeting Muslim communities has also incited new ways of misinterpreting Qur’anic text to further marginalize them. Second-generation Muslim Americans are responding to Islamophobia by reframing the negative depictions about their identities through community-based activism. This paper takes an intersectionality approach to understanding how Muslims across the New York metro area are managing their religious identities as they seek to develop a sense of belonging in American society. This ethnographic case study addresses how second-generation Muslims are resisting Islamophobia through community building, civic engagement, and college student associations. Countering Islamophobia has become part of the everyday life experience for Muslims in New York and is currently their main trajectory for integration into American society.